GENETIC VARIABILITY OF INDONESIAN PAPAYA ACCESSIONS AS REVEALED BY RANDOM AMPLIFIED POLYMORPHIC DNA AND MORPHOLOGICAL CHARACTERIZATION - Riry Prihatini; Tri Budiyanti; Noflindawati Noflindawati (Indonesian Agency for Agricultural Research and Development, 2019)
Diverse papaya (Carica sp.) accessions are found in many regions in Indonesia, but their genetic diversity have not yet been studied. Random Amplified Polymorphic DNA (RAPD) is a simple yet accurate method that can be used to examine the genetic diversity of papaya. The study aimed to examine the genetic diversity of Indonesian papaya accessions using RAPD markers and morphological characters. The RAPD was applied on 23 papaya accessions using 30 primers. The appearing bands were further analyzed with the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) and Principal Component Analysis (PCA). The molecular results were then compared to the fruit morphological data, including fruit shape, size, flesh color, texture, and flavor. The RAPD analysis revealed that the 23 papaya accessions clustered into six main clades with Dice-Sorensen coefficient similarity ranged from 0.71 to 0.98. The first group consisted of 11 accessions, including both the hybrids and local accessions. The second group consisted of eight accessions especially six Indonesian hybrids, a Mexican Hybrid and a Hawaiian hybrid. The other four groups had a single member namely Sicincin Panjang, Lokal Sumani, Cariso, and Carica. The molecular grouping, however, did not align with the fruit character grouping. Overall, it was implied that the Indonesian papaya accessions were genetically narrow, of which some accessions were closely related to Hawaiian and Mexican accessions. These results can be used as a reference on papaya crossbreeding program in Indonesia.